The influence of networking, individual effort, and time management on research performance of academics at Malaysian research universities - Tauhed, Siti Zainab; Mohd. Rasdi, Roziah; Ibrahim, Rahinah; Abu Samah, Bahaman (Corporación Educativa SER, 2019)
This study examined the personal resources that influence research performance of academics at the Malaysian Research Universities (MRUs). This study adopted correlational design and proportionate stratified random sampling was used to select 377 samples of academics at MRUs. Questionnaire survey was employed and the descriptive statistics and multiple regressions were used to analyse the data. The results show that individual efforts significantly influences research performance. This study is important for the university's management and Human Resource Development practitioners to identify factors, and outline efficient strategies and interventions to enhance academics' research performance.